Upper respiratory tract symptoms and salivary immunoglobulin A of elite female gymnasts: a full year longitudinal field study - Dumortier, J.; Bishop, N. C.; Vogelaers, D.; Boone, J.; Delesie, L.; Tobback, E.; Mariman, A.; Bourgois, J. G. (Biology of Sport, 2020)
The aim of this study was to determine the frequency of upper respiratory tract symptoms (URS) in elite female gymnasts during a training season. In addition, we aimed to observe the extent to which salivary immunoglobulin A (sIgA) is associated with URS in these athletes, including potential effects of the season and timing of sample collection. Over one year, 18 elite female gymnasts completed URS and fatigue questionnaires weekly and provided 1 mL of saliva after a minimum 36 h of rest (morning or afternoon) to measure relative sIgA concentration (= mean absolute sIgA value of the week divided by the mean absolute sIgA value of the weeks without URS). Mean weekly URS and mean relative sIgA values per gymnast correlated negatively (r = -0.606, P = 0.022). Most URS were noted in the most fatigued gymnasts (7.4 ± 10.1 vs. 2.5 ± 5.6 (P < 0.001) for `normal` and 2.1 ± 3.7 (P = 0.001) for `better than normal` rested). In spring, relative sIgA was higher compared to autumn (112 ± 55 vs. 89 ± 41%, P < 0.001) and winter (92 ± 35%, P = 0.001), while during summer, relative sIgA appeared higher compared to autumn (110 ± 55 vs. 89 ± 41%, P = 0.016). The interaction effect with timing of sample collection showed higher relative sIgA values in morning samples in spring and summer compared to afternoon samples, with the inverse observed in autumn and winter (F = 3.565, P = 0.014). During a gymnastics season, lower relative sIgA values were linked to higher susceptibility to URS in elite gymnasts. However, relative sIgA values were influenced by season and timing of sample collection and thus should be considered when interpreting sIgA data.